Technical trading in Asia based on E/P ratio - Do, Hong Nhung (2013)
Our first major finding is the positive correlation between the dependent variable - market return and the following independent variables: E/P ratio, short spread and long spread in the Asian and Oceanian markets. However, the results are not statistically significant. Secondly, we have constructed three different investment portfolios: switching portfolio using short spread, switching portfolio using long spread and benchmark portfolio. We have found out that most of the switching portfolios using short spread outperform the other two. Again, the differences are not significant. Findings of this study are of importance for investors who are keen on investing in Asian and Oceanian equity markets. Moreover, this is the first paper to conduct a comprehensive study in a wide range of Asian countries. Therefore, the paper serves as foundation for future research.